2022
DOI: 10.1155/2022/6738068
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Emotions for People with Autism: An Approach to Improve Skills

Abstract: Autism spectrum disorder refers to a neurodevelopmental disorders characterized by repetitive behavior patterns, impaired social interaction, and impaired verbal and nonverbal communication. The ability to recognize mental states from facial expressions plays an important role in both social interaction and interpersonal communication. Thus, in recent years, several proposals have been presented, aiming to contribute to the improvement of emotional skills in order to improve social interaction. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Autism Spectrum Disorder (ASD) is a developmental disorder that involves persistent challenges in social interaction, verbal and non-verbal communication, and restricted/repetitive behaviors. Previous studies (Bandrés et al, 2022), (Gillies-Walker et al, 2022), (Dantas & Nascimentodo, 2022) showed that the use of computing technologies can complement the learning activities of students’ with autism through improved communication, better interactions and enhanced skills. Consequently, a significant number of research (Aburukba et al, 2017), (Chien et al, 2015), (Winoto & Tang, 2017), (Leonidis et al, 2017) focused on the development of interactive digital learning tools, also known as assistive technologies, to enable interactions and interoperability between the person diagnosed with ASD and their caregivers.…”
Section: Introductionmentioning
confidence: 98%
“…Autism Spectrum Disorder (ASD) is a developmental disorder that involves persistent challenges in social interaction, verbal and non-verbal communication, and restricted/repetitive behaviors. Previous studies (Bandrés et al, 2022), (Gillies-Walker et al, 2022), (Dantas & Nascimentodo, 2022) showed that the use of computing technologies can complement the learning activities of students’ with autism through improved communication, better interactions and enhanced skills. Consequently, a significant number of research (Aburukba et al, 2017), (Chien et al, 2015), (Winoto & Tang, 2017), (Leonidis et al, 2017) focused on the development of interactive digital learning tools, also known as assistive technologies, to enable interactions and interoperability between the person diagnosed with ASD and their caregivers.…”
Section: Introductionmentioning
confidence: 98%